Akibat Hukum Perkawinan di Bawah Tangan terhadap Istri, Anak, dan Harta Kekayaan dalam Perspektif Hukum Islam dan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Nurhasan Nurhasan; Fitri Yani (Universitas Batanghari Jambi, 2019)
Marriage is a sacred part of life, because it must pay attention to norms and rules in society. But for various reasons, marriage is often done in a variety of models of marriage. Like an underhand marriage. An underhand marriage is a marriage that has fulfilled the harmony and conditions of the marriage but has not stated the marriage to the competent authority as stipulated in the legislation. The purpose of this study is to reveal the legal consequences of the marriage results under the hand of his wife, children and property from Islamic Law and Law Number 1 of 1974 concerning Marriage in the hope that awareness of every Indonesian citizen arises to register marriages so that children's rights can well guaranteed. The methodology used is normative juridical, the results of research are that there are still many Indonesian people who do not understand the general provisions regarding the recording requirements and also do not understand the legal consequences that will occur to those who do the marriage under the hand.